Mechacical properties of Ductile Cast Iron at different carbon equivelent and cast thickness - Omran, Abdel-Nasser; Abdel-Jaber, G.T.; Abeul-Kareem, Abeul-Kareem (IJRDO-Journal of Applied Science, 2019)
Recently, Ductile or spheroidal Graphite Iron (SGI) emerged as a replacement to other types of cast iron owing to some specific applications. Because, it has good mechanical properties, better castability, machinability, and thermal resistance. This work investigates the mechanical properties of the produced ductile cast iron (SGI) at different CE and different thickness. The results indicated that Hardness, UTS, and yield strength for all values of the residual Mg increased by increasing CE and at the same CE %, the hardness, UTS, and yield strength decreased by increasing the section thickness from 20 mm to 80 mm. The Maximum hardness UTS, and yield strength values of the produced SGI alloys obtained in this study were 237 HB, 570 Mpa, and 319Mpa respectively. Elongation for all values of nodularity decreased by increasing CE, and at the same CE%, elongation increased by increasing the section thickness from 20 mm to 80 mm. Hardness, UTS, and yield strength increased by increasing the pearlite content in the matrix but elongation decreased.